THU0155 Predictors of Low Disease Activity and Remission after One Dose of Golimumab in Patients with Rheumatoid Arthritis. (10th June 2014) - Dasgupta, B.; Combe, B.; Durez, P.; Schulze-Koops, H.; Louw, I.; Wollenhaupt, J.; Zerbini, C.; Beaulieu, A.; Yao, R.; Huyck, S.; Govoni, M.; Weng, H.H.; et al.
Abstract : Background: Patients with rheumatoid arthritis (RA) who respond well to biologics early in treatment tend to have better outcomes. Identifying baseline characteristics that predict early response may facilitate effective patient segmentation and treatment strategies. Objectives: To identify baseline factors that may predict very early low disease activity (LDA) and remission after 1 dose of golimumab (GLM) in patients with active RA in GO-MORE, a study resembling typical clinical practice. Methods: GO-MORE was an open-label, multinational, prospective study in biologic-naïve patients with active RA despite disease-modifying antirheumatic drug (DMARD) therapy. Patients received 50-mg subcutaneous GLM once monthly for 6 months. In post hoc analyses, potential baseline predictors of LDA (28-joint disease activity score using erythrocyte sedimentation rate [DAS28-ESR] ≤3.2) after 1 month (1 dose) were first evaluated in univariate models. Factors were evaluated in a stepwise fashion; those with significant associations ( P <.10) were included in a final multivariate model. A similar analysis procedure evaluated predictors of achievement of remission (DAS28-ESR <2.6) after 1 month of treatment. Results: At baseline in 3280 efficacy-evaluable patients (82.8% female), mean age was 52.3 years, mean disease duration was 7.6 years, and mean DAS28–ESR was 5.97 (SD=1.095). After 1 month of GLM treatment, 16.6% (545/3280) of patients achieved LDA, and 7.7% (251/3280) achieved remission. 1 In initial analyses predicting LDA, nonsignificant factors ( P ≥.10) were smoking status, number of failed DMARDs, methotrexate dose, and disease duration. In the final regression model, female sex was associated with lower likelihood of LDA at 1 month (odds ratio [OR]=0.668, P =.0016). Greater likelihood of LDA was associated with younger age (continuous variable, OR=0.987, P =.0029), absence of comorbidities (OR=1.470, P =.0020), lower baseline tender joint count (TJC28; OR=0.892, P <.0001), lower swollen joint count (SJC28; OR=0.970, P=. 0185), lower patient global assessment of disease activity (PGA; OR=0.991, P=. 0013), lower Health Assessment Questionnaire (HAQ) score category (HAQ≥1.75 vs 0 to 1.125; OR=0.706, P=. 0150), and lower ESR (OR=0.453, P <.0001). In the final multivariate model predicting remission at 1 month, age, comorbidities, TJC28, and ESR were the only significant predictors. Conclusions: In a broad population of patients with active RA treated in typical clinical practice settings in many countries, predictors of early LDA after 1 dose of GLM therapy (achieved by 16.6% of patients) included younger age; female sex; absence of comorbidities; and lower baseline ESR, TJC28, SJC28, PGA, and HAQ. References: Combe B et al. Ann Rheum Dis. doi:10.1136/annrheumdis-2013-203229. Accessed 16 Dec 2013. Disclosure of Interest: : B. Dasgupta Grant/research support: EULAR, ACR, Health Technology Assessment, British Heart Foundation, Research for Patient Benefit UK, and Napp, Consultant for: Schering-Plough, Merck, Roche, Mundipharma, and Astra Zeneca, B. Combe Grant/research support: Pfizer and Roche-Chugai, Consultant for: Merck, Pfizer, Roche-Chugai, and UCB, P. Durez: None declared, H. Schulze-Koops Grant/research support: Abbott, Actelion, Biotest, BMS, Chugai, Essex, GSK, MSD, Medac, Merck, Mundai Pharma, Novartis, Nycomed, Pfizer, Roche, and UCB, Consultant for: Abbott, Actelion, Biotest, BMS, Chugai, Essex, GSK, MSD, Medac, Merck, Mundai Pharma, Novartis, Nycomed, Pfizer, Roche, and UCB, Speakers bureau: Abbott, Actelion, Biotest, BMS, Chugai, Essex, GSK, MSD, Medac, Merck, Mundai Pharma, Novartis, Nycomed, Pfizer, Roche, and UCB, I. Louw Grant/research support: Merck, BMS, Pfizer, Roche, Janssen, and Lilly, Consultant for: Abbott, BMS, and Janssen in South Africa, and the Merck Investigator Consulting Network, J. Wollenhaupt Consultant for: Abbott, Biotest, BMS, Chugai, MSD, Medac, Merck, MSD, Pfizer, Roche, and UCB, Speakers bureau: Abbott, Biotest, BMS, Chugai, MSD, Medac, Merck, MSD, Pfizer, Roche, and UCB, C. Zerbini Grant/research support: Novartis, Pfizer, Bristol, Lilly, Amgen, and MSD, Consultant for: Pfizer, Bristol, Lilly, and MSD, and nonremunerative position of influence as board member for Pfizer and Bristol, A. Beaulieu Grant/research support: Novartis, Merck, Servier, Amgen, AbbVie, Celgene, Pfizer, Lilly, and Roche, R. Yao Employee of: Merck, S. Huyck Employee of: Merck, M. Govoni Employee of: Merck, H. Weng Employee of: Merck, N. Vastesaeger Employee of: Merck DOI: 10.1136/annrheumdis-2014-eular.2258